Studi Kualitatif Penyalahgunaan Ganja Dikalangan Mahasiswa Di Jakarta Selatan Tahun 2023 - Cindy Portinari Savega; Suraya, Izza (LPPM Sekolah Tinggi Ilmu Kesehatan Pekanbaru Medical Center, 2024)
The negative impact that marijuana has on the brain and mental health of its users is huge, and this has an impact on social activities, especially among university students. The prevalence of cannabis abuse in Indonesia among students is 3.2%. This study aims to explore more deeply the use of marijuana among university students in South Jakarta. The research approach used is qualitative with phenomenological methods. The data collection technique applied is in-depth interviews with students who use marijuana. The unit of analysis that is the focus of this study involves students who use marijuana as the main informants, counselors as key informants, and people closest to the main informants as supporting informants. The sampling method used also involves the snowball technique to select marijuana user informants. The results of this study reveal that marijuana abuse among students is influenced by various factors such as peer influence, economic motives, and availability and ease of access. Cannabis abuse has significant impacts, including changes in social behavior, mental impacts such as anxiety, and physical impacts such as weight loss.